The Study Personification in Story “Lao Folk Tales” Compile by Kidaeng Phonekasermsouk - SATHAMMA, Phothong; XAYVONGSAN, Chanthaphone; SIRIKOUN, Somphet; CHANTHAPHONE, Lattana (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The objective of the research aims to study the types of idiomatic personification that appear in the storybook “Lao Folktales’ book2” which is to approach the qualitative study in order to analyze the secondary data from the storybook on Lao Folktales’book 2 in accordance with those theories’ determination. The main finding of the research found that: all idiomatic personifications were occurred 30 idioms and divided into 3 categories: Non-living Personification, Living Personification, and Supernatural Personification as the following details: Non-living personification comprised of 2 things: Natural Personification had got 1 idiom equaled 3.33% and Inventive or constructional Personifications found 1 idiom covered 3.33%. Living Personification consisted of 2 things: Animal Personification had got 23 idioms equaled 76.66% and Plant Personification found 2 idioms covered 6.66%. Supernatural Personification discovered 1 thing: Individual Personification had got 3 idiomsequaled10%. Based on the result of the research revealed that the animal personification had found the most idiom which demonstrated as 23 idioms covered 76.66% and the personification which the least appeared in the storybook there were: Natural Personification had got 1 idiom equaled 3.33% and Inventive or constructional. Personifications found 1 idiom covered 3.33% whilst the human personification and the power personification were not found.